A polynomial approach for reflection, transmission, and ellipsometric parameters by isotropic stratified media - El-Agez, Taher; Taya, Sofyan; El Tayyan, Ahmed (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
A polynomial approach for the calculation of the reflectance, the transmittance, and the ellipsometric parameters of a stratified isotropic planar structure is presented. We show that these parameters can be written in a very simple and compact form using the so-called elementary symmetric functions that are extensively used in the mathematical theory of polynomials. This approach is applied to quarter-wave Bragg reflectors. The numerical results reveal an exact match with the well known matrix formalism.
Optica Applicata, Vol. 40, 2010, nr 2, s. 501-510
Keywords: optyka; ellipsometry; reflectance; transmittance; ellipsometric parameters; quarter-wave Bragg reflectors; stratified planar structure